Soluble vascular cell adhesion molecular-1 is a potential biological indicator of hemophilic arthropathy. Issue 46 (November 2016) - Tseng, Yu-Hsin; Chiou, Shyh-Shin; Zeng, Yu-Sheng; Tsai, Shih-Pien; Chen, Chun-Shih; Liao, Yu-Mei; Lin, Pei-Chin
Abstract : Abstract: Hemophilic arthropathy is the most common chronic complication in patients with hemophilia. The pathogenesis of hemophilic arthropathy involves the inflammatory processes associated with rheumatoid arthritis (RA). Determining the severity and/or progression of joint damage is crucial when evaluating the effect of treatment modalities. Identifying reliable biomarkers in the peripheral blood of patients with hemophilic arthropathy may be beneficial in clinical practice. Circulating soluble vascular cell adhesion molecule-1 (sVCAM-1), E-selectin, and P-selectin levels are elevated in patients with RA. Our study investigated whether these soluble adhesion molecules can be used as biological indicators in the course of joint damage in patients with hemophilia A. Patients with hemophilia A (mild, moderate, and severe) were enrolled. The plasma levels of sVCAM-1, E-selectin, and P-selectin in patients with hemophilia A and control were measured using specific enzyme-linked immunosorbent assay kits. Joint damages were evaluated using Pettersson scores. No statistically significant differences were observed in E-selectin and P-selectin levels between patients and controls. The sVCAM-1 level was significantly higher in patients with hemophilia A than in controls. The differences remained significant in patients with severe hemophilia A but not in patients with mild or moderate hemophilia A. The degree of hemophilic arthropathy was evaluated using Pettersson scores, and a score higher than 5 indicated marked arthropathy. Patients with more than 1 joint with marked arthropathy showed significantly higher sVCAM-1 levels. sVCAM-1 levels in patients with hemophilia A are associated with the severity of hemophilic arthropathy.